Hierarchical Intrafibrillarly Mineralized Collagen Membrane Promotes Guided Bone Regeneration and Regulates M2 Macrophage Polarization - Xuan, Yaowei; Li, Lin; Ma, Muzhi; Cao, Junkai; Zhang, Zhen (Frontiers in Bioengineering and Biotechnology, 2022)
Mineralized collagen has been introduced as a promising barrier membrane material for guided bone regeneration (GBR) due to its biomimetic nanostructure. Immune interaction between materials and host significantly influences the outcome of GBR. However, current barrier membranes are insufficient for clinical application due to limited mechanical or osteoimmunomodulatory properties. In this study, we fabricated hierarchical intrafibrillarly mineralized collagen (HIMC) membrane, comparing with collagen (COL) and extrafibrillarly mineralized collagen (EMC) membranes, HIMC membrane exhibited preferable physicochemical properties by mimicking the nanostructure of natural bone. Bone marrow mesenchymal stem cells (BMSCs) seeded on HIMC membrane showed superior proliferation, adhesion, and osteogenic differentiation capacity. HIMC membrane induced CD206+Arg-1+ M2 macrophage polarization, which in turn promoted more BMSCs migration. In rat skull defects, HIMC membrane promoted the regeneration of new bone with more bone mass and more mature bone architecture. The expression levels of Runx2 and osterix and CD68 + CD206 + M2 macrophage polarization were significantly enhanced. HIMC membrane provides an appropriate osteoimmune microenvironment to promote GBR and represents a promising material for further clinical application.